Endometriosis in the Adolescent Patient - Stuparich, Mallory A.; Donnellan, Nicole M.; Sanfilippo, Joseph S. (Seminars in Reproductive Medicine, 2017)
The recognition and management of endometriosis in the adolescent patient is challenging. A strong clinical suspicion for endometriosis should be maintained in the adolescent who suffers from acyclic pelvic pain as well as absenteeism from school and lack of participation in daily activities. Risk factors include the presence of an obstructive Mullerian anomaly, a family history of endometriosis, and conditions that prolong exposure to endogenous and exogenous estrogens. Empiric medical therapy with nonsteroidal anti-inflammatory drugs and combined oral contraceptive pills may be considered in most adolescents with endometriosis. Failure of empiric therapy may warrant diagnostic laparoscopy, which affords a concomitant opportunity for treatment via excision of endometriosis. Endometriotic implants in the adolescent tend to be more atypical, appearing red/flame-like, clear/polypoid, or vesicular. Endometriosis tends to recur more often in adolescents when compared with adults, and the role of postoperative medical therapy for the suppression of disease progression is not entirely clear. Current knowledge on the impact of adolescent endometriosis on future fertility is limited but overall reassuring.
Keywords: adolescent; endometriosis; laparoscopy